Initial characterization of print awareness in unhoused children - Hoffmann, Anne; Little, Lauren; Vincent, Kristen; Lui, Karen; Pabalan, Laura (Frontiers in Psychology, 2024)
This study provides an initial understanding of print awareness, a foundational literacy skill, in a group of 12 unhoused children at two shelters in a large urban setting. Children ranged in age from 4;1 to 8;0, representing grades associated with learning to read (i.e., pre-kindergarten to second grade). Findings indicate that the majority of children in this sample were significantly delayed in their acquisition of print awareness skills. Caregivers were surveyed regarding their beliefs about supporting literacy development and what would be beneficial for helping them in this area. Responses indicated that almost all caregivers believed that some literacy development should occur outside of the school setting and that it would be helpful if they (the caregivers) were taught both what skills to teach and how to teach them.